Hubungan Self Efficacy, Pelibatan Orang Tua, dan Self Determination Dengan Kemandirian Belajar Peserta Didik - Wwidya, Sherrin nurlita; Setiyowati, Arbin Janu; Atmoko, Adi (Jurnal Pendidikan (Teori dan Praktik), 2023)
Independent learning is one of the main factors in the success of students. This study aims to determine the correlation between self-efficacy, parental involvement, and self-determination with the learning independence of  high school Surabaya students. The correlational design involved 390 samples. Data were collected through four scales with item validity test ≥ 0.3 and Cronbach Alpha reliability of 0.6 - 0.770, then analyzed by multiple linear regression. The regression results show that (sig F (172) = 0.000 <0.05) there is a simultaneous significant correlation between self-efficacy, parental involvement, and self-determination with learning independence. The contribution of the three predictors in the model together is 57.30% on learning independence.